(untitled) (Bangladesh Journal of Child Health, 2020)
Dyskeratosis congenita is a rare type of inherited bone marrow failure syndromes (IBMFs) characterized by ectodermal dysplasia, bone marrow failure and cancer predisposition. Accelerated telomere shortening is supposed to be the causal mechanism of this disease. Features of ectodermal dysplasia appears early and may give clues of suspicion of forthcoming bone marrow disease. It has variable presentation and severe form of disease presents earlier. This a case report on a 2 year 2-month old boy who presented with features of bone marrow failure and had abnormality of skin, nail and oral mucosa. Bangladesh J Child Health 2020; VOL 44 (2) :122-125